Prevalence of congenital sensorineural deafness in a population of client‐owned purebred kittens in the United Kingdom - Lorenzo Mari; Julia Freeman; Jan Van Dijk; Luisa De Risio (Journal of Veterinary Internal Medicine, 2019)
Abstract Background Data about congenital sensorineural deafness (CSD) in white blue‐eyed cats derive mainly from research colonies, and information about client‐owned cats is limited. Objectives To describe the prevalence of CSD in a client‐owned population of white purebred kittens and colored littermates in the United Kingdom. Animals One hundred thirty‐two solid white client‐owned purebred kittens and 61 colored littermates, 6 to 21 weeks of age. Methods Retrospective (56 cases) and prospective (137 cases) study. Hearing was assessed by brainstem auditory evoked response testing, and the entire litter was tested. Results Congenital sensorineural deafness was diagnosed only in solid white kittens, with a prevalence of 30.3% (15.9% bilateral, 14.4% unilateral). The prevalence of CSD was significantly higher in white kittens with 1 (44.4%) or 2 (50%) blue irises than in those without blue irises (22.2%). Kittens with at least 1 blue iris were 3.2 times more likely to have CSD than kittens without blue irises. In solid white kittens, CSD was diagnosed in 7 of 15 (46.7%) Turkish Vankedisi, 8 of 18 (44.0%) Maine Coon, 18 of 41 (43.9%) Norwegian Forest, 3 of 11 (27.3%) British Shorthair, 2 of 12 (16.7%) Devon Rex, 2 of 12 (8.3%) Persian, 1 of 21 (4.8%) Russian, and 0 of 2 Sphinx. The prevalence of CSD was significantly different in Norwegian Forest, Maine Coon, and Turkish Vankedisi kittens compared with Persian or Russian kittens. Conclusion and Clinical Importance We identified a high prevalence of CSD in a population of client‐owned purebred white kittens in the United Kingdom and suggest differences in breed‐specific prevalence of CSD.